Inhibition of apoptosis of activated hepatic stellate cells by tissue inhibitor of metalloproteinase-1 is mediated via effects on matrix metalloproteinase inhibition: implications for reversibility of liver fibrosis. - Murphy, F; Issa, R; Zhou, X; Ratnarajah, S; Nagase, H; Arthur, M; Benyon, C; Iredale, J (2002)
The activated hepatic stellate cell (HSC) is central to liver fibrosis as the major source of collagens I and III and the tissue inhibitors of metalloproteinase-1 (TIMP-1). During spontaneous recovery from liver fibrosis, there is a decrease of TIMP expression, an increase in collagenase activity, and increased apoptosis of HSC, highlighting a potential role for TIMP-1 in HSC survival. In this report, we use tissue culture and in vivo models to demonstrate that TIMP-1 directly inhibits HSC apoptosis. TIMP-1 demonstrated a consistent, significant, and dose-dependent antiapoptotic effect for HSC activated in tissue culture and stimulated to undergo apoptosis by serum deprivation, cycloheximide exposure, and nerve growth factor stimulation. A nonfunctional mutated TIMP-1 (T2G mutant) in which all other domains are conserved did not inhibit apoptosis, indicating that inhibition of apoptosis was mediated through MMP inhibition. Synthetic MMP inhibitors also inhibited HSC apoptosis. Studies of experimental liver cirrhosis demonstrated that persistent expression of TIMP-1 mRNA determined by PCR correlated with persistence of activated HSC quantified by alpha smooth muscle actin staining, while in fibrosis, loss of activated HSC correlated with a reduction in TIMP-1 mRNA. We conclude that TIMP-1 inhibits apoptosis of activated HSC via MMP inhibition.